The Making of a Script: Cretan Hieroglyphic and the Quest for Its Origins - Ferrara, Silvia (Bulletin of ASOR, 2021)
What is the origin of the earliest script in Europe? Is it invented locally or borrowed from an external template? How can we go about addressing this problem? A common view is that the script in question, Cretan Hieroglyphic, is locally created but externally inspired, probably through an influence from Egypt. But this appreciation should be the result of a full examination of the evidence, rather than a superficial appraisal of the script signs. This article reframes this approach, starting with generic assessments on origin and stimulus, and so opens a new avenue that takes into account the following aspects: 1) the establishment of a methodology for cross-comparisons between the Egyptian and Cretan scripts; 2) the situated context of the Egyptian and Cretan scripts in the mid-3rd to late 3rd millennium b.c.e.; 3) the local Cretan seal imagery; and 4) case studies of sign shapes, representing physical and immaterial referents across the Egyptian Hieroglyphic and Cretan repertoires. Only from this broad, multicentric framework, which has input from archaeology, epigraphy, iconography, and paleography, can we establish a solid method to address the origin of Cretan Hieroglyphic.